Effects of Dietary Supplementation of β‐hydroxy‐β‐methylbutyrate on Sow Performance and mRNA Expression of Myogenic Markers in Skeletal Muscle of Neonatal Piglets. Issue 1 (23rd December 2015) - Wan, HF; Zhu, JT; Shen, Y; Xiang, X; Yin, HJ; Fang, ZF; Che, LQ; Lin, Y; Xu, SY; Feng, B; Wu, D
Contents: The effects of dietary β ‐hydroxy‐ β ‐methylbutyrate (HMB) supplementation during gestation on reproductive performance of sows and the mRNA expression of myogenic markers in skeletal muscle of neonatal pigs were determined. At day 35 of gestation, a total of 20 sows (Landrace × Yorkshire, at third parity) were randomly assigned to two groups, with each group receiving either a basal diet or the same diet supplemented with 4 g/day β ‐hydroxy‐ β ‐methylbutyrate calcium (HMB‐Ca) until parturition. At parturition, the total and live litter size were not markedly different between treatments, however, the sows fed HMB diet had a decreased rate of stillborn piglets compared with the sows fed the control (CON) diets (p < 0.05). In addition, piglets from the sows fed HMB diet tended to have an increased birth weight (p = 0.08), and a reduced rate of low birth weight piglets (p = 0.05) compared with piglets from the CON sows. Nevertheless, lower feed intake during lactation was observed in the sows fed the HMB diet compared with those on the CON diet (p < 0.01). The relative weights of the longissimus dorsi (LD) and semitendinosus (ST) muscle were higher (p < 0.05) in neonatal pigs from the HMB than the CON sows. Furthermore, maternal HMB treatment increased the mRNA levels of the myogenic genes, including muscle regulatory factor‐4 (MRF4, p < 0.05), myogenic differentiation factor (MyoD) and insulin‐like growth factor‐1 (IGF‐1, p < 0.01). In conclusion, dietary HMB supplementation to sows at 4 g/day from day 35 of gestation to term significantly improves pregnancy outcomes and increases the expression of myogenic genes in skeletal muscle of neonatal piglets, but reduces feed intake of sows during lactation.